2021
DOI: 10.3390/s21144638
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Post-Fall Detection Using the Cross-Dataset: Feature Vectors, Classifiers and Processing Conditions

Abstract: In this study, algorithms to detect post-falls were evaluated using the cross-dataset according to feature vectors (time-series and discrete data), classifiers (ANN and SVM), and four different processing conditions (normalization, equalization, increase in the number of training data, and additional training with external data). Three-axis acceleration and angular velocity data were obtained from 30 healthy male subjects by attaching an IMU to the middle of the left and right anterior superior iliac spines (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…For SVM, results have been mixed: Igual and colleagues [13] found that SVM or neural network classifiers worked either well or only moderately depending on the dataset on which they were trained, but no accidental falls were investigated. Similarly, Koo et al [31] found that SVM and ANN classifiers may work well in internal testing but during external testing only when training data were subjected to a number of preprocessing steps. Of note, they used their own laboratory data for training and validated on the SisFall dataset, but not on accidental falls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For SVM, results have been mixed: Igual and colleagues [13] found that SVM or neural network classifiers worked either well or only moderately depending on the dataset on which they were trained, but no accidental falls were investigated. Similarly, Koo et al [31] found that SVM and ANN classifiers may work well in internal testing but during external testing only when training data were subjected to a number of preprocessing steps. Of note, they used their own laboratory data for training and validated on the SisFall dataset, but not on accidental falls.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for better performance might have been that training data were impact aligned using the SampEn algorithm. Impact alignment was recently shown to improve classifier performance by Koo and colleagues [31] using a different technique for event detection. Some previously published algorithms reached extremely high performance values up to 100% sensitivity or accuracy (e.g., [60,61]) while others are of similar value as in our study (e.g., [29,42,44,62]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Post fall intelligence is an important research area in the field of fall detection as it can be useful in determining various post fall injuries [ 18 ] and serve as an intelligence parameter [ 19 ] for doctors. Koo et al [ 20 ] present experiments for post fall detection from a combination of self collected data and the SisFall dataset. They conduct tests using sliding windows as well as discrete windows from these signals and compute statistical features from them.…”
Section: Literature Reviewmentioning
confidence: 99%